Eblaitica : essays on the Ebla archives and Eblaite language. - Gordon, Cyrus H. (Cyrus Herzl), 1908-2001; Rendsburg, Gary (Eblaitica: Essays on the Ebla Archives and the Eblaite Language., 2002)
The fourth and final volume in the series Eblaitica: Essays on the Ebla Archives and Eblaite Language embodies eight cogent essays by a variety of specialists. Of particular interest in this issue is the second part of Michael Astour's history of Ebla. Contributors include Alfonso Archi, Michael C. Astour, Cyrus H. Gordon, Gary A. Rendsburg, Robert R. Stieglitz, and Al Wolters.